Ga(III) pyridinecarboxylate complexes: potential analogues of the second generation of therapeutic Ga(III) complexes - Rendošová, Michaela; Gyepes, Róbert; Sovová, Simona; Sabolová, Danica; Vilková, Mária; Olejníková, Petra; Kello, Martin; Lakatoš, Boris; Vargová, Zuzana (JBIC, Journal of biological inorganic chemistry, 2023)
A series of novel Ga(III)-pyridine carboxylates ([Ga(Pic)3]·H2O (GaPic; HPic = picolinic acid), H3O[Ga(Dpic)2]·H2O (GaDpic; H2Dpic = dipicolinic acid), [Ga(Chel)(H2O)(OH)]2·4H2O (GaChel; H2Chel = chelidamic acid) and [Ga(Cldpic)(H2O)(OH)]2 (GaCldpic; H2Cldpic = 4-chlorodipicolinic acid)) have been synthesized by simple one-step procedure. Vibrational spectroscopy (mid-IR), elemental analysis, thermogravimetric analysis and X-ray diffraction confirmed complexes molecular structure, inter and intramolecular interactions and their influence to spectral and thermal properties. Moreover, complex species speciation was described in Ga(III)-HPic and Ga(III)-H2Dpic systems by potentiometry and 1H NMR spectroscopy and mononuclear complex species were determined; [Ga(Pic)2]+ (logβ021 = 16.23(6)), [Ga(Pic)3] (logβ031 = 20.86(2)), [Ga(Dpic)2]- (logβ021 = 15.42(9)) and [Ga(Dpic)2(OH)]2- (logβ-121 = 11.08(4)). To confirm the complexes stability in 1% DMSO (primary solvent for biological testing), timescale 1H NMR spectra were measured (immediately after dissolution up to 96 h). Antimicrobial activity evaluated by IC50 (0.05 mM) is significant for GaDpic and GaCldpic against difficult to treat and multi-resistant P. aeruginosa. On the other hand, the GaPic complex is most effective against Jurkat, MDA-MB-231 and A2058 cancer cell lines and significantly also decreases the HepG2 cancer cells viability at 75 and 100 μM concentrations in a relatively short time (up to 48 h). In addition, fluorescence measurements have been used to elucidate bovine serum albumin binding activity between ligands, Ga(III) complexes and bovine serum albumin.
Keywords: Serum Albumin, Bovine; molekulární struktura; Neoplasms; sérový albumin hovězí; Cell Line; Pyridines; Ligands; pyridiny; buněčné linie; Humans; Coordination Complexes; ligandy; nádory; lidé; Molecular Structure; komplexní sloučeniny